Aspects of an induced magnetic field utilization for heat and mass transfer ferromagnetic hybrid nanofluid flow driven by pollutant concentration - Shuguang Li; Rania Saadeh; J.K. Madhukesh; Umair Khan; G.K. Ramesh; Aurang Zaib; B.C. Prasannakumara; Raman Kumar; Anuar Ishak; El-Sayed M. Sherif (Case Studies in Thermal Engineering, 2024)
In the growing need for energy and heightened environmental considerations, the effective control and optimization of thermal processes and transferring mass are of utmost importance. Engine oil and water-based nanofluids have emerged as potential solutions for various industrial applications, from energy generation to sophisticated manufacturing. Because of these demands, the current work aims to explore the need and significance of its research field, providing insights into crucial elements of heat and mass transport properties in the presence of hybrid nanofluids. This work investigates the impact of an induced magnetic field, including hybrid nanoparticle circulation across a stretched surface with an endo/exothermic chemical reaction and the concentration of waste discharge effects. The acquired ordinary differential equations (ODEs) were solved using the Runge Kutta Fehlberg 45 technique. The findings show that engine oil leads to effectiveness in heat transfer, while water-based hybrid nanofluid performs better mass transfer. While motor oil works well in an endothermic situation, water-based hybrid nano liquid has a noticeable effect on heat transfer over the activation energy component in an exothermic chemical reaction process. Further, water-based nanofluids exhibit lower pollutant levels than engine oil when exposed to local pollutant external source parameter. These results provide essential guidance for choosing the best nanofluid for a given engineering problem, leading to greater effectiveness and productivity in various applications, including advanced cooling systems, chemical manufacturing, pharmaceuticals, waste treatment, and pollutant dispersion control.